중등 영어 교사의 학습동기: 동기유발 전략 분석 도구 개발 및 활용도 분석 - 맹은경; 이상민 (중등영어교육, 2019)
Motivation is the most significant component to influence students’ language learning. In an EFL(English as a Foreign Language) situation, it is often difficult to motivate students intrinsically or integratively. Teachers’ motivational strategies play a key role to increase students’ motivation. The current study developed a framework to guide secondary English teachers’motivational strategies and evaluate them based on the two most widely accepted motivation models in learning, Keller’s ARCS model and Dornyei’s motivational model. The framework is comprised of four categories. Each of the four categories has multiple sub-categories. Factor analysis was used to confirm the validity of each category, sub-category and item. In addition, the revised and confirmed model was used to investigate the secondary English teachers’ behavior of using motivational strategies. The results showed the teachers used motivational strategies most frequency in the categories of confidence and satisfaction. Futhermore, the teachers’ English proficiencies, not the students’ English proficiencies, was the major factor in influencing their use of motivational strategies.
Keywords: 동기; 동기유발 전략; 교사 영어 구사능력; 학습자 영어능력; motivation; motivational strategies; teachers’ L2 proficiency; learners’L2 proficiency